2007
DOI: 10.1117/12.700792
|View full text |Cite
|
Sign up to set email alerts
|

Miniature infrared gas sensors using photonic crystals

Abstract: The sensitivity of an infrared gas sensor depends on the interaction length between radiation and gas, i.e. a reduction in cell size generally results in a reduced sensitivity, too. However, low group velocity regions in the bandstructure of photonic crystals should enable the realization of very compact gas sensors. Using photonic crystals based on macroporous silicon experimental results with CO2 show an increase of the gas sensitivity in the photonic crystal compared to an empty cell of same dimensions. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…), and metal oxides (SiO 2 , TiO 2 , Al 2 O 3 , WO 3 ). Experiment has shown that PhCs can be applied in practically all types of optical gas sensors, including PhC gas sensors based on spectroscopic absorption (Lambrecht et al 2007 ;Jensen et al 2008 ;Pergande et al 2011 ) , resonance properties (Wang et al 2007 ;Sünner et al 2008 ;Awad et al 2010 ) , surface electromagnetic waves (Colodrero et al 2008 ;Hidalgo et al 2009 ;Hidalgo et al 2010 ) , and self-collimation effects (Wang et al 2008b ) . These sensors can detect a wide range of gases (O 2 , CO 2 , NO 2 , VOCs, N 2 , etc.…”
Section: Photonic Crystals In Gas Sensorsmentioning
confidence: 98%
See 2 more Smart Citations
“…), and metal oxides (SiO 2 , TiO 2 , Al 2 O 3 , WO 3 ). Experiment has shown that PhCs can be applied in practically all types of optical gas sensors, including PhC gas sensors based on spectroscopic absorption (Lambrecht et al 2007 ;Jensen et al 2008 ;Pergande et al 2011 ) , resonance properties (Wang et al 2007 ;Sünner et al 2008 ;Awad et al 2010 ) , surface electromagnetic waves (Colodrero et al 2008 ;Hidalgo et al 2009 ;Hidalgo et al 2010 ) , and self-collimation effects (Wang et al 2008b ) . These sensors can detect a wide range of gases (O 2 , CO 2 , NO 2 , VOCs, N 2 , etc.…”
Section: Photonic Crystals In Gas Sensorsmentioning
confidence: 98%
“…When the PhC slow light structure is introduced into the sample cell, the interaction of light and matter will be enhanced, so the absorption coef fi cient can be greatly increased, and this technology offers a potential for the realization of small and high sensitivity sensors (Lambrecht et al 2007 ) .…”
Section: Photonic Crystals In Gas Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the greater the electric field overlap with the analyte, the greater the effective absorption by the medium. [15] In recent years, some researchers in Denmark [16] and Germany [17,18] have found that the photonic crystal waveguide is able to enhance the light-matter interaction. If we introduce one or several line defects in the photonic crystal (as Figure 5a shows), then the line defects could damage the periodicity of the photonic crystal, appearing as defect states Compared with the velocity of the normal light (3 Â 10 8 m=s), not only do the new gas sensors made up of new optical devices have better sensitivity, but also the volume of the gas cells has been decreased.…”
Section: Changing the Light Velocity To Increase The Interaction Betwmentioning
confidence: 99%
“…In 2007, using macroporous silicon photonic crystals as gas cell, Lambrecht et al [18] designed a miniature CO 2 sensing system. In 2008, Jensen et al, [16] using one-dimensional photonic crystal, designed an O 2 sensing system.…”
Section: Changing the Light Velocity To Increase The Interaction Betwmentioning
confidence: 99%